Magnetohydrodynamics unsteady separated stagnation-point (USSP) flow of a hybrid nanofluid on a moving plate - Khashi'ie, Najiyah Safwa; Wahid, Nur Syahirah; Md Arifin, Norihan; Pop, Ioan (John Wiley & Sons, 2022)
In view of the unique properties in the hybrid nanofluids, this working fluid has been widely applied in industrial and technological sectors along with the substantial growth of numerical and experimental studies. Hence, this study contributes to the thermal characteristics and flow behavior of magnetohydrodynamics (MHD) unsteady separated stagnation point (USSP) flow of Cu-Al2O3/water nanofluid in a two-dimensional system considering the shifting plate. The results are generated using the bvp4c package by first reducing the governing model. The results show that for the decelerating flow case, dual solutions exist while the steady and accelerating flow cases admit a unique solution. The critical values (separation from laminar to turbulent flow) and separation values (separation from attached flow solution/AFS to reverse flow solution/RFS) are observed and collected for different Hartmann number, acceleration parameter and fluids. The Cu-Al2O3/water nanofluid has the maximum thermal rate followed by Cu-water and pure water. Meanwhile, the magnetic field and acceleration parameter are also the contributing factors for the thermal enhancement and the expansion of the boundary layer separation.